Redox status of high‐mobility group box 1 performs a dual role in angiogenesis of colorectal carcinoma. Issue 9 (23rd June 2015) - Zhu, Lingyin; Ren, Lin; Chen, Yingxuan; Fang, Jingyuan; Ge, Zhizheng; Li, Xiaobo
Abstract During inflammation, high‐mobility group box 1 in reduced all‐thiol form (at‐HMGB1) takes charge of chemoattractant activity, whereas only disulfide‐HMGB1 (ds‐HMGB1) has cytokine activity. Also as pro‐angiogenic inducer, the role of HMGB1 in different redox states has never been defined in tumour angiogenesis. To verify which redox states of HMGB1 induces angiogenesis in colorectal carcinoma. To measure the expression of VEGF‐A and angiogenic properties of the endothelial cells (ECs), at‐HMGB1 or ds‐HMGB1 was added to cell medium, further with their special inhibitors (DPH1.1 mAb and 2G7 mAb) and antibodies of corresponding receptors (RAGE Ab and TLR4 Ab). Also, a co‐culture system and conditioned medium from tumour cells were applied to mimic tumour microenvironment. HMGB1 triggered VEGF‐A secretion mainly through its disulfide form interacting with TLR4, while co‐operation of at‐HMGB1 and RAGE mediated migratory capacity of ECs. Functional inhibition of HMGB1 and its receptors abrogated HMGB1‐induced angiogenic properties of ECs co‐cultured with tumour cells. HMGB1 orchestrates the key events of tumour angiogenesis, migration of ECs and their induction to secrete VEGF‐A, by adopting distinct redox states.